Environmental and control studies of the common scab disease of potatoes caused by Actinomyces scabies (Thaxt.) Guss. - Dippenaar, B. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Agric.) -- University of Stellenbosch, 1933.